Rifted subjects, fractured Earth: 'Progress' as learning to live on a self-transforming planet. Issue 2 (March 2022) - Clark, Nigel; Szerszynski, Bron
In this article we make a case for an understanding of human difference that attends to the way that social collectives engage with the Earth's own capacity for self-differentiation. This draws us into conversation with recent interpretations of Hegel that see at the heart of his philosophy not a self-aggrandizing human agent set against a passive nature but an inherently fractured subject confronting a no-less intrinsically sundered outer reality. We use the example of traditional open-field cultural burning to show how skilled operators can painstakingly develop responses to ecoclimatic variability, putting this into dialogue with Hegel's reflections on the 'incendiarism' of political revolution as a human expression of the wider self-antagonism of nature. We go on to make connections between Hegel's account of the way that subjects can anticipate their own futurity and Indigenous conceptions of non-linear time, suggesting that the emergence of new earth-oriented practices can be seen as a complex interrelation of past, present and future. We close by suggesting that 'progress' for Hegel is not about the collective subject achieving omniscience and omnipotence, but involves the onerous and harrowing coming to terms with both its own divided identity and its exposure to a discordant external reality.